2012
DOI: 10.1155/2012/979563
|View full text |Cite
|
Sign up to set email alerts
|

Intracystic Papillary Carcinoma of the Breast: Report of Three Cases and Literature Review

Abstract: Intracystic papillary carcinoma is a rare malignant tumor of the breast. It occurs communally in postmenopausal women. Clinically it can be asymptomatic or manifested by a breast mass or a nipple discharge. On imaging intracystic papillary carcinoma has usually benign features. Pathologic diagnosis can be difficult at classical histological examination and identification of myoepithelial cells layer by immunohistochemical study can be useful. In the majority of cases of pure intracystic papillary carcinoma, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 15 publications
1
21
0
2
Order By: Relevance
“…This is unlike the many reports on encapsulated papillary carcinoma [6][7][8][9] and even the intracystic variety [10,11]. Of course, explanations were attempted in all of them (Table 2) (Figure 2).…”
Section: Discussionmentioning
confidence: 88%
“…This is unlike the many reports on encapsulated papillary carcinoma [6][7][8][9] and even the intracystic variety [10,11]. Of course, explanations were attempted in all of them (Table 2) (Figure 2).…”
Section: Discussionmentioning
confidence: 88%
“…Ultrasound guided core biopsy of suspected intra cystic mass has been suggested by many authors to differentiate benign from malignant papillary neoplasms but failed to distinguish in situ from invasive papillary carcinoma as invasion is found in peripheral part of the tumor [9]. Tomonori et al [10] also suggested necessity of excisional biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Those have been studied by Immunohistochemical targeting these proteins which demonstrated linear and continuous basement membranes in benign and in situ lesions and discontinuous or absent expression in invasive carcinoma [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, nipple discharge may be the first sign (4). On ultrasonography (US) it may appear cystic, semi solid or solid (5). Microcalcifications may accompany the lesion on mammograms (4).…”
Section: Introductionmentioning
confidence: 99%
“…Although treatment methods are still controversial, surgery remains the treatment of choice (3). Endocrine therapy and radiation therapy are used in most medical centers but the evidence indicating that this method improves prognosis is still insufficient (5). Two patients with IPC who were treated at our clinic are presented together with the relevant literature.…”
Section: Introductionmentioning
confidence: 99%